2012
DOI: 10.1007/s11104-012-1334-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the effect of zinc deficiency on Arabidopsis growth and mineral concentrations

Abstract: Aims Zinc deficiency is a common micronutrient deficiency in plants growing in many different regions of the world and is associated with disturbances in uptake and accumulation of mineral nutrients. Despite many published data on physiological factors affecting ion accumulation in Zn deficient plants, there is very little information about the genetic factors underlying this. We aim to identify genetic loci involved in mineral accumulation and plant performance under Zn deficiency. Methods Genetic loci were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The co-localization of QTLs may reflect the correlations observed between the ionomic traits. Based on A. thaliana QTL analysis, different ionomic traits demonstrated significant correlation which most robust was the correlations between Zn, Mn, and Fe traits 16 , 42 . The result of co-localization frequency of ionomic QTLs on detected MQTLs regions in this study revealed the possible signs of MQTLs interaction, which impacts the association of ionomic traits at the genomic level.…”
Section: Discussionmentioning
confidence: 99%
“…The co-localization of QTLs may reflect the correlations observed between the ionomic traits. Based on A. thaliana QTL analysis, different ionomic traits demonstrated significant correlation which most robust was the correlations between Zn, Mn, and Fe traits 16 , 42 . The result of co-localization frequency of ionomic QTLs on detected MQTLs regions in this study revealed the possible signs of MQTLs interaction, which impacts the association of ionomic traits at the genomic level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no overlap between leaf and seed Zn concentrations was found and very little overlap in QTLs for ion concentrations when plants were grown in soil or hydroponics. This was obvious even in the same RIL populations under controlled greenhouse conditions, potentially indicating that rhizosphere-related processes and internal plant remobilization have a significant impact on Zn storage ( Ghandilyan et al, 2009 , 2012 ). The low resolution in QTL mapping further imposes difficulties to identify causal individual genes that explain a significant part of the trait variance within the population.…”
Section: Introductionmentioning
confidence: 95%
“…Deficiency of Zn is a common problem in different regions (Ghandilyan et al, 2012). Optimum soybean yield can be obtained when Zn and P concentrations in the soil are greater than extension recommendations (Anthony et al, 2012a).…”
Section: Ajabsmentioning
confidence: 99%